2017
DOI: 10.1590/s1519-99402017000400007
|View full text |Cite
|
Sign up to set email alerts
|

Biometric viscera and blood parameters of meat quails supplemented with inorganic selenium and vitamin E

Abstract: SUMMARY This study aimed to evaluate biometric viscera and blood parameters of quails at 14 and 35 days of age, supplemented with different levels of inorganic selenium and vitamin E. A completely randomized design was used in a 4×4 factorial scheme (inorganic Se = 0.1125, 0.2250, 0.3375 and 0.4500 mg/kg diet x VE = 10, 23, 36 and 49 IU/kg feed). In the 0-14 days experiment, 2,400 newborn quail were used, distributed in 16 treatments and three replications of 50 birds each. In the 14-35 days experiment, 1,680 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Determination of biochemical parameters in the blood is a tool that assists in the diagnosis of metabolic diseases. (12) Tsekhmistrenko et al (13) proposed that high concentrations of sodium-selenite in the diet would lead to greater accumulation of selenium in the brain, heart, and liver, causing disease. Despite differences in serum creatinine and glucose levels between the study groups, the rest of the serum parameters did not differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of biochemical parameters in the blood is a tool that assists in the diagnosis of metabolic diseases. (12) Tsekhmistrenko et al (13) proposed that high concentrations of sodium-selenite in the diet would lead to greater accumulation of selenium in the brain, heart, and liver, causing disease. Despite differences in serum creatinine and glucose levels between the study groups, the rest of the serum parameters did not differ.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe and the United States, supplementation with inorganic forms of selenium is permitted to a maximum level of 0.50 mg/kg while the organic forms are allowed up to 0.30 mg/kg. (12) Previous studies suggested that the use of inorganic selenium is more limited considering the possible toxic effects. (13) Although this fact appears obvious in broilers and laying hens, it is not so clear in quail.…”
Section: Introductionmentioning
confidence: 99%